Clinical Profile and Socio-Demographic Characteristics of Children with Severe Acute Malnutrition (SAM) in Southern Odisha - Mathew, Shine Merin; Kumar, T V Ram; Niranjan, Mohanty (Journal of Nepal Paediatric Society, 2021)
Introduction: Severe acute Malnutrition (SAM) is an important contributor to morbidity and mortality amongst less than five years of age. In the National Family health Survey (NFHS), it was seen that 10% of children with SAM would require hospital admission. Even with establishment of nationwide Nutritional Rehabilitation centres (NRC) and standard guidelines, the problem of SAM is high in Odisha. The present study was undertaken to look at the clinical profile of the children with SAM in southern Odisha. Methods: A prospective observational study was conducted from one month to 60 months of age with SAM who were admitted to a tertiary teaching hospital. Demographics, clinical features, laboratory tests were recorded and tabulated. Results: We enrolled 70 SAM children (screened = 3288) for our study who were primarily nutritional. Exclusive breast feeding till six months was present in 26%, and all had inadequate complementary feeding. The major clinical presentations of SAM were diarrhea (36%), fever (34%) and poor weight gain (29%). Conclusions: Majority of SAM had low birth weight, and had poor rates of exclusive breast feeding, inadequate complementary feeding, and recurrent infections.